Transversal Competences and Employability: The Impacts of Distance Learning University According to Graduates' Follow-Up - Pedro Abrantes; Ana Paula Silva; Bárbara Backstrom; Cláudia Neves; Isabel Falé; Marc Jacquinet; Maria do Rosário Ramos; Olga Magano; Susana Henriques (MDPI AG, 2022)
Since higher education qualifications and digital transition are considered key factors for economic development and individual opportunities, distance learning has been presented as a solution to improve the labor force's skills and employability. However, such links were seldom studied systematically in specific contexts, and doubts exist regarding online programs. Based on the results of three successive follow-up surveys to the graduates of the Portuguese distance learning public university (Universidade Aberta), from 2011 to 2018 (n = 1358), our article examines the graduates' perception of acquired transversal competences, in relation to employability and social mobility gains. The statistical analysis points out a positive perception of transversal competences development, especially analytical capacity, autonomy, and communication, although some concerns were raised regarding digital skills, teamwork, job search skills, and social capital. The impacts on employability and socioeconomic mobility are positive for most students, but variable according to analyzed competences, and tend to occur mostly through internal mobility rather than through job search skills or entrepreneurship. Although exploratory, such findings allow some final considerations regarding the effective ability of higher education distance learning to enhance economic growth and employability, through transversal competences, as well as to sketch some suggestions to improve such ability.